KAJIAN USAHA BUDIDAYA RUMPUT LAUT DI DESA ILODULUNGA KECAMATAN ANGGREK KABUPATEN GORONTALO UTARA - Rauf, Marlin; Dien, Christian R; Aling, Djuwita R.R (Universitas Sam Ratulangi, 2016)
Abstract This study aims to determine the social conditions of farmers seaweed, and to know the production system and financial analysis of seaweed farming in the village Ilodulunga. The education level ever taken by the farmers seaweed. Village Ilodulunga amounted to 78.26% of primary school graduates, SMK graduates much as 4.35%, and amounted to 17.39% of high school graduates. The productive age seaweed farmers in the village Ilodulunga ie from the age of 20-70 years. Having work experience of over 10 years, have a high motivation to work and about 50% have had a permanent home, and 50% is semi-permanent. Seaweed farming production system that takes into account facilities and cultivation techniques that include aquaculture site selection, installation of floating rope, planting, maintenance of seaweed seedlings, harvesting and post-harvest and marketing. Seaweed farming in the village Ilodulunga eligible to run because it has operating profit or absolute advantage Rp. 145.264 million, net profit of Rp. 129 360 833, the profit rate (rate of profit) amounted to 422%, 223% Profitability, BCR sale of BEP 5.2 Rp. 17,516,429, 1,751 kg BEP unit, and the repayment period is 0,447 years (5 months, 10 days, 19 hours). Keywords: Business, Aquaculture, seaweed, and Gain. Â Abstrak Penelitian ini bertujuan untuk mengetahui keadaan sosial pembudidaya rumput laut, serta untuk mengetahui sistem produksi dan analisis finansial usaha budidaya rumput laut yang ada di Desa Ilodulunga. Tingkat pendidikan yang pernah di tempuh oleh pembudidaya rumput laut. di Desa Ilodulunga lulusan SD sebesar 78,26% , lulusan SMP Sebesar 4,35%, dan lulusan SMA sebesar 17,39%. Umur produktif para pembudidaya rumput laut di Desa Ilodulunga yaitu dari umur 20-70 tahun. Memiliki pengalaman kerja diatas 10 tahun, memiliki motivasi kerja yang tinggi dan sekitar 50% telah memiliki rumah permanen dan 50% masih semi permanen. Sistem produksi budidaya rumput laut yaitu dengan memperhatikan fasilitas dan teknik budidaya yang meliputi pemilihan lokasi budidaya, pemasangan tali apung, penanaman bibit, pemeliharaan bibit rumput laut, panen dan pasca panen, dan pemasarannya. Usaha budidaya rumput laut di Desa Ilodulunga layak untuk dijalankan karena memiliki operating profit atau keuntungan absolut sebesar Rp. 145.264.000, net profit sebesar Rp. 129.360.833, profit rate ( tingkat keuntungan) sebesar 422%, Rentabilitas 223%, BCR 5,2 BEP penjualan Rp. 17.516.429, BEP satuan 1.751 kg, dan Jangka waktu pengembalian yaitu 0,447 tahun (5 bulan, 10 hari, 19 jam). Kata Kunci : Usaha, Budidaya, rumput laut, dan Keuntungan.